The development of a graphene oxide-based aptasensor used for the detection of tetracycline in honey. Issue 7 (7th February 2017) - Tang, Yali; Zhang, Jichuan; Liu, Jia-Hui; Gapparov, Ilyar; Wang, Sai; Dong, Yiyang; Su, Haijia; Tan, Tianwei
Abstract : The absorption properties of graphene oxide and its aggregation ability in saline were used for detecting antibiotic tetracycline. Abstract : Herein, an ultrasensitive and selective assay for antibiotic tetracycline (TC) was developed based on an aptamer and graphene oxide (GO). The assay was designed based on the protection effect of the aptamer on GO due to aggregation. When the GO-based aptasensor was incubated with TC, TC could capture the TC aptamer from GO, leading to the aggregation of GO in a high salt solution. The increase in size and decrease in zeta-potential can be detected by adding TC in the assay. A linear relationship between the optical response and the logarithm concentration of TC was observed after centrifugation. The detection range was 0.002 to 20 ng mL −1 and the detection limit was 0.001 ng mL −1 (S/N = 3). The recoveries of TC in honey samples (0.001 mg kg −1, 0.01 mg kg −1 and 0.1 mg kg −1 ) were from 82.5% to 117%.